INCREASING THE FERTILITY OF SALINE SOILS OF THE LOWER AMUDARYO (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article presents information on soil salinity and changes in soil nutrients during the cultivation of cotton and winter wheat in the farms of Chimbay, Amudarya districts of the Republic of Karakalogistan.